Effect of APAP and heated humidification with a heated breathing tube on adherence, quality of life, and nasopharyngeal complaints - Nilius, Georg; Franke, Karl J.; Domanski, Ulrike; Schroeder, Maik; Ruhle, Karl H. (Sleep & breathing, 2016)
Purpose Positive airway pressure (PAP) therapy adherence can be affected by rhinitis sicca and xerostomia complaints. Additional heated humidification (HH) is the appropriate method when such complaints arise. The aim of this study was to determine if HH with a supplementary heated breathing tube can increase adherence, reduce subjective nasopharyngeal complaints (NPC), and improve sleepiness (ESS: Epworth Sleepiness Scale) and quality of life (FOSQ: Functional Outcome of Sleep Questionnaire). Methods We subdivided 72 obstructive sleep apnea (OSA) patients into two groups before therapy initiation. The NPC risk group consists of subjects with NPC and the low-risk group without. The risk group was identified by a score of > 9 in a 5-item 25-point NPC questionnaire and pathological ESS. All patients were eligible for automatic CPAP devices (APAP), which were randomly configured with or without HH during 6 weeks. Results The adherence differences with and without HH were not significant in the NPC risk group (330 ± 103 vs. 281 ± 118 min/night) and in the low-risk group (330 ± 116 vs. 321 ± 89). NPC and ESS scores in the risk group were both significantly reduced with HH. Daily function (FOSQ) in the risk group was significantly improved with HH (90.0 ± 11.9 vs. 82.0 ± 12.0 ( p < 0.05)). Conclusion HH showed a tendency to improve APAP adherence. The adherence in both groups was quite high, and for that reason, it is difficult to show a statistically significant effect. A differentiation into NPC risk groups before starting PAP treatment is useful. HH reduces side effects and sleepiness and improves quality of life in an NPC risk group.